Efikasi diri dan kecemasan karir mahasiswa tingkat akhir - Surya, Aldo; Sofiah, Diah; Farhanindya, Hikmah Husniyah (SUKMA : Jurnal Penelitian Psikologi, 2025)
Uncertainty in obtaining decent employment can lead to increased anxiety among university students. This condition is often triggered by intense job market competition, negative perceptions of the professional world, and rising demands for individual qualifications. This study aims to identify the relationship between self-efficacy and career anxiety among undergraduate students in the final stage of their academic studies. A quantitative approach with a correlational research design was employed, involving 129 final-semester students from the undergraduate psychology program at University of 17 Agustus 1945 Surabaya, enrolled in the 2018–2019 cohorts during the study period. The instruments used were the Career Anxiety Scale developed by Tsai et al. (2017) and a self-efficacy scale based on the theoretical framework proposed by Bandura (1997). Data were analyzed using the Pearson Product Moment correlation technique. The results indicated a strong negative correlation between self-efficacy and career anxiety. Higher levels of self-efficacy were associated with lower levels of career-related anxiety. Self-efficacy accounted for 40.45% of the variance in career anxiety, suggesting a substantial influence. Ketidakpastian mendapat pekerjaan yang layak dapat menyebabkan munculnya kecemasan di kalangan mahasiswa, yang dipicu oleh persaingan kerja yang semakin ketat, pandangan negatif terhadap dunia kerja, serta meningkatnya tuntutan terhadap kualifikasi individu. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara efikasi diri dengan kecemasan karir pada mahasiswa yang berada pada tahap akhir studi sarjana. Penelitian ini menggunakan pendekatan kuantitatif dengan desain korelasional pada 129 mahasiswa semester akhir program studi sarjana psikologi Universitas 17 Agustus 1945 Surabaya yang terdaftar pada angkatan 2018-2019 selama masa periode penelitian Instrumen pengukuran penelitian ini menggunakan career anxiety scale yang dikembangkan Tsai, et al (2017) dan skala efikasi diri merujuk konsep teoritis oleh Bandura (1997). Analisis data dilakukan dengan teknik korelasi product moment. Hasil penelitian ini menunjukkan bahwa peningkatan efikasi diri berhubungan erat dengan kecemasan karir. Semakin tinggi tingkat efikasi diri maka akan semakin rendah kecemasan karir pada mahasiswa. Efikasi diri memiliki pengaruh dengan kecemasan karir sebesar 40,45% menunjukkan adanya pengaruh yang kuat.